Frequency, Causes and Pattern of Presentation of Impacted Maxillary Canine, A Clinical and Radiographic Study - KIRAN, SAMERA; NAZIR, ASIF; KHALIQ, FAHAD; RAZA ZAHID, MUHAMMAD; FAYYAZ, AFROZA; ALISHBAH, ANOOSH (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Toassess frequency, causes and pattern of presentation of maxillary canine impaction. Method: This cross-sectional study was conducted from August 2022 to July 2023 at Oral & Maxillofacial Surgery Department and Orthodontic Department of Nishtar Institute of Dentistry, Multan. A total of 84 patients with 96 impacted maxillary canines matching inclusion and exclusion criteria were included in the study. Patient demographic data, clinical and radiographic findings were recorded and all the data were collected on a specially designed proforma. Data were analyzed using SPSS version 22 and frequencies, percentages, ratios, means ± SD were calculated. Results: Overall frequency of canine impaction in all patients presenting was 3.5%. A male to female ratio of (30%:70%) 1:2.5 with female predominance was found. There was more occurrence of unilateral impacted maxillary canine than bilateral with a ratio of 6:1 and more palatally impacted canines than buccal once (75%:25%). Conclusion: Overall frequency of canine impaction in local population was low. The most common cause of maxillary canine impaction was a mismatch in jaw size and tooth size followed by wrong line and long path of eruption.Frequency of odontogenic pathology associated with maxillary impacted canine was low. The most common type of canine impaction was palatal followed by buccal one. The most common clinical diagnostic indicator for impacted canine was presence of palatal or buccal buldge. Radiologically, most of the canine impactions fall in Sector III grade and type II in relation to root of adjacent lateral incisor